And, what comes next? - Rodríguez Gázquez, María de los Ángeles (Investigación y Educación en Enfermería, 2015)
Investigación y Educación en Enfermería is going through a great moment as a serial scientific publication with its current indexation in prestigious national and international bibliographic bases, which is an essential requisite to improve the visibility required by globalization, allowing access to the journal by any nurse anywhere in the planet. A big challenge that we expect to fulfill shortly is to increase the number of citations received in articles from other journals, a direct indicator that reveals the repercussion within the academic community of the knowledge embodied in our pages. Another challenge, perhaps the most important of all, is that we must continue our efforts to continue publishing more and better articles that show innovative alternatives to solve theoretical and practical problems, which are a daily challenge for Nursing. Big challenges await, which with effort and support from the authors, reviewers, members of the editorial and scientific committees, and from our dear readers we will be able to successfully meet, making of Investigación y Educación en Enfermería a better and better publication. How to cite this article: Rodríguez-Gázquez MA. And, what comes next? Invest Educ Enferm. 2015; 33(1): 7.